Mitochondrial DNA Diversity of Tor douronensis Valenciennes (Cyprinidae) in Malaysian Borneo - Yuzine, Esa; Siti Shapor, Siraj; Siti Khalijah, Daud; Khairul Adha, A. Rahim; M.T, Abdullah; Jeffrine Rovie, Ryan Japning; Soon Guan, Tan (2004)
This study examines the population structure and taxonomy ofTor douronensis, an important indigenous freshwater fish species in Malaysian Borneo, by using sequence analysis of 466 base pairs of the mitochondrial cytochrome coxidase I (COl) gene. A total of 62 fish samples were collected from five locations in Sarawak (N=54) and Sabah (N=8). The phylogenetic analysis using the NeighbourJoining (N]) method supported the monophyletic status between T. douronensis and Tor tambroides, which further reinforced their taxonomic status as distinct species. The T.douronensis haplotypes werefurther divided into three major groups, with the Pelian[uhfrom Sabah forming its own group (Cluster Ill) with strong bootstrap support. The large genetic differences separating the Sabah haplotypesfrom its Sarawak congeners suggested that the Pelian fish might represent a cryptic species. The current study showed high levels of intra and inter-population variations in T. douronensis. Within all population variations, T. douronensis populations werefound, except in Bario. The presence offixed haplotype differences along with high FST values among the populations ofT. douronensis, support the conclusion that little or no migration occurred among the extant populations separated by large geographic distances or river systems. However, the sharing of haplotypes between some such papulations, for example between Batang Ai and Bario (HS6), and between Batang Ai and Ulu Limbang/Ba Kelalan (HS2) provided support that T. douronensis had a historically widespread natural distribution in the region probably during the Quaternary period. Overall, the present study was able to shed light on the taxonomy and population structure of T. douronensis in Malaysian Borneo.